3D‐Printed Metal–Organic Framework‐Derived Composites for Enhanced Photocatalytic Hydrogen Generation. Issue 10 (7th August 2022) - Hussain, Mian Zahid; Großmann, Paula F.; Kohler, Fabian; Kratky, Tim; Kronthaler, Laura; van der Linden, Bart; Rodewald, Katia; Rieger, Bernhard; Fischer, Roland A.; Xia, Yongde
Abstract : Direct ink writing technique is used to 3D print Ti‐metal–organic framework (MOF) NH2 ‐MIL‐125 mixed with boehmite dispersal. Pt is also deposited onto 3D‐printed monolith using atomic layer deposition (ALD) to offer additional catalytic sites. The Ti‐MOF‐derived powder sample and the pyrolyzed 3D‐printed monolith samples are evaluated for photocatalytic H2 evolution under UV–vis light. As a proof of concept, herein, it is demonstrated that 3D‐printed MOF‐derived monolith photocatalysts show five times higher H2 evolution performance compared with TiO2 /C powder sample due to better interaction between 3D‐printed photocatalysts and the incident light. The high surface area, the formation of hierarchical macro‐ to nanopores, and the optimizable shape/size of the 3D‐printed catalyst maximize the exposure of catalytic active sites to incident photons and increase their photocatalytic H2 evolution performance. In addition, the N‐functionalized porous carbon from organic linker, and the uniformly distributed Pt/PtO x species deposited by ALD, provide cocatalytic active sites for photocatalytic reaction and further enhance photocatalytic activity 30% of 3D‐printed monoliths. This work on the 3D‐printed MOF‐derived free‐standing monoliths for photocatalytic application provides a readily available approach to further fabricate a variety of 3D‐printed MOF‐based and derived materials for different energy and environment applications. Abstract : Monolith composites derived from 3D‐printed Ti‐MOF NH2 ‐MIL‐125 mixed with boehmite are promising photocatalysts for H2 evolution under UV–vis light and exhibit HER performance five times higher than Ti‐MOF‐derived TiO2 /C powder sample. Moreover, deposition of Pt onto 3D‐printed monolith by atomic layer deposition approach provides additional active sites and further enhances photocatalytic HER activity 30% of 3D‐printed monoliths.